2020
DOI: 10.1002/ptr.6878
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein L5 mediated inhibition of c‐Myc is critically involved in sanggenon G induced apoptosis in non‐small lung cancer cells

Abstract: Though Sanggenon G (SanG) from root bark of Morus alba was known to exhibit anti‐oxidant and anti‐depressant effects, its underlying mechanisms still remain unclear. Herein SanG reduced the viability of A549 and H1299 non‐small lung cancer cells (NSCLCs). Also, SanG increased sub‐G1 population via inhibition of cyclin D1, cyclin E, CDK2, CDK4 and Bcl‐2, cleavages of poly (ADP‐ribose) polymerase (PARP) and caspase‐3 in A549 and H1299 cells. Of note, SanG effectively inhibited c‐Myc expression by activating ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Guangsangon L (145) − 389.3 [74] M. macroura [74]; M. yunanensis [23] Soroceal B (146) + 137.5 [13] M. alba [13] Soroceal (147) + 365 [90] M. nigra [128]; S. bonplandii [90] Morusalbanol A (148) #…”
Section: Dehydroprenyl-2-arylbenzofuran Type Mdaas (Type A)mentioning
confidence: 99%
“…Guangsangon L (145) − 389.3 [74] M. macroura [74]; M. yunanensis [23] Soroceal B (146) + 137.5 [13] M. alba [13] Soroceal (147) + 365 [90] M. nigra [128]; S. bonplandii [90] Morusalbanol A (148) #…”
Section: Dehydroprenyl-2-arylbenzofuran Type Mdaas (Type A)mentioning
confidence: 99%
“…Numerous studies have reported that RPL5 was involved in the progression of various malignant tumors [6][7][8][9]. The pan-cancer gene expression patterns were performed to examine the differential expression of RPL5 across TCGA cancer types.…”
Section: Rpl5 Expression In Normal Tissues and Pan-cancermentioning
confidence: 99%
“…The ribosomal protein RPL5 is a component of the ribosome, a large ribonucleoprotein complex responsible for protein synthesis in cells. RPL5 is involved in the development and progression of a variety of tumors, such as melanoma [6], liver cancer [7], breast cancer [8], and non-small cell lung cancer [9]. However, the role and regulation mechanism of RPL5 has not been revealed in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Park et al's paper [6], to detect cell death, HCT116 or SW480 cells were treated with Morusin (5 µM) for 24 h, and incubated with TUNEL assay mixture for 60 min by using the DeadEnd™ Fluorometric TUNEL system kit (Promega, Madison, WI, USA).…”
Section: Tunel Assaymentioning
confidence: 99%
“…It is well documented that c-Myc is a biomarker for poor prognosis of CRC patients, as it is a transcription factor that is critically associated with cell growth, cell adhesion, proliferation, and apoptosis [6]. Hence, to target c-Myc has been considered a good strategy for prevention or treatment of CRCs [7].…”
Section: Introductionmentioning
confidence: 99%